Pengaruh Inflasi, Suku Bunga dan Nilai Tukar terhadap Return Saham yang Terdaftar di IDX-MES BUMN 17 Periode 2018-2022 - Jihan Mawaddah; Eko Susanto; Andi Amri (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study is to investigate the effects of interest rates, inflation, and currency exchange rates on stock returns for businesses that are listed between 2018 and 2022 on IDX-MES BUMN 17. List the three macroeconomic factors that have an impact on the performance of the stock return of the firm and what those factors mean. A technique using linear regression analysis is used to determine each company's degree of influence. This study employs a purposive sample approach in addition to secondary data from corporate financial reports and macroeconomic data. The results of this study demonstrate that inflation, interest rates, and currency values ​​all have a significant and positive influence on stock returns, some of which have an effect concurrently. The goal of this research's results is to assist investors, financial professionals, and decision-makers in making more intelligent and prudent financial decisions. Furthermore, this study can contribute to the body of information in academic literature about the impact of macroeconomic factors on stock returns.